Effects of adjuvant radiotherapy on completely resected gastric cancer: A radiation oncologist's view of the ARTIST randomized phase III trial. Issue 1 (October 2015) - Yu, Jeong Il; Lim, Do Hoon; Ahn, Yong Chan; Lee, Jeeyun; Kang, Won Ki; Park, Se Hoon; Park, Joon Oh; Park, Young Suk; Lim, Ho Yeong; Kim, Seung Tae; Kim, Sung; Sohn, Tae Sung; et al.
Abstract Purpose We investigated which subgroups might benefit from adjuvant radiotherapy (RT) and suggested optimal RT targets by analyzing the results of the Adjuvant Chemoradiation Therapy in Stomach Cancer (ARTIST) trial. Methods We conducted randomized controlled trial in 458 gastric cancer patients. Patients were randomly assigned to XP (6 cycles of capecitabine and) or XPRT (2 cycles of XP + RT 45 Gy/25 fraction with capecitabine + 2 cycles of XP) groups after D2 resection. Minimum follow-up was 5 years. Results During follow-up, 77 patients (33.8%) in the XP arm and 60 (26.1%) in the XPRT arm experienced recurrence. Among these patients, locoregional recurrence (LRR) developed in 44 (9.6%; 29 in XP, 15 in XPRT; P = 0.03). The local recurrence rate (4.8%) did not vary between arms. Regional recurrence was the most important difference between the two groups (23 in the XP arm, 5 in the XPRT arm, P < 0.001). LRR-free survival (LRRFS) was significantly different between study arms (P = 0.03), especially in patients with LN metastasis (P = 0.009). Conclusions Adjuvant RT after D2 resection in gastric cancer reduced LRR, especially in group 3 LNs, and improved LRRFS. Patients with LN metastasis benefited more from the adjuvant RT treatment than the other subgroups.